2008
DOI: 10.1063/1.2832771
|View full text |Cite
|
Sign up to set email alerts
|

Controlling domain wall pinning in planar nanowires by selecting domain wall type and its application in a memory concept

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 8 publications
(7 reference statements)
2
87
0
1
Order By: Relevance
“…For nanowire-based MRAM devices, the required bistable operation is achieved by moving a DW between two pinning positions along a wire (figure 2a). These pinning sites are generally asymmetric in nature, with lower fields or currents required to move a DW back across an MRAM cell to switch the element than to remove the DW from the element altogether [24,56]. This has even been extended using DW-chirality-dependent switching to create multi-bit memories [56].…”
Section: Current Applicationsmentioning
confidence: 99%
“…For nanowire-based MRAM devices, the required bistable operation is achieved by moving a DW between two pinning positions along a wire (figure 2a). These pinning sites are generally asymmetric in nature, with lower fields or currents required to move a DW back across an MRAM cell to switch the element than to remove the DW from the element altogether [24,56]. This has even been extended using DW-chirality-dependent switching to create multi-bit memories [56].…”
Section: Current Applicationsmentioning
confidence: 99%
“…The magnetization direction in such magnetically soft nanowires is defined by the geometry of the nanowire, and when structural features such as notches are patterned within the nanowire, the spin structure tends to follow the local edges of these features. It was recently reported that different DW structures will experience different pinning interactions with a single triangular notch structure, 4,[7][8][9] since the spin configuration through a structurally asymmetric feature presents different energetic barriers to a propagating DW depending upon the micromagnetic spin structure of the wall. This energetic difference manifests itself as a difference in the magnetic field required to push the wall through a structural pinning feature.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In such devices information is encoded in the magnetization direction of domains in planar nanowires, with the nucleation and propagation of DWs in nanowires allowing for the input, manipulation, and readout of stored information. Domain walls have been considered to behave as quasiparticles 5 that can be controlled by external magnetic fields, spin-polarized currents, and lithographically patterned variations in the nanowire geometry, such as notches.…”
Section: Introductionmentioning
confidence: 99%
“…More details on the scanning electron microscopy, electron beam lithography and lift-off techniques are available in Refs [8,22,23,56].…”
Section: Methodsmentioning
confidence: 99%
“…Different techniques have been utilized to fabricate these structures, but electrodeposition has been proved to be simple, fast and a low cost technique, as well as using this technique, it is possible to produce different materials and multilayer as: thin films, nanowires or nanotubes [5,8,11,12,14,18,31].…”
Section: Introductionmentioning
confidence: 99%